We know the derivative of ex, which is ex.
(ex)' = ex
We can find the derivative of e√sinx using chain rule.
Find ᵈʸ⁄dₓ, if
y = e√sinx
Let u = sinx.
y = e√u
Let v = √u.
y = ev
Now,
y = ev ----> y is a function of v
v = √u ----> v is is a function of u
u = sinx ----> u is is a function of x
By chain rule, the derivative of y with respect to x :
Substitute y = ev, v = √u and u = sinx.
Substitute v = √u.
Substitute u = sinx.
Therefore,
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 04, 25 08:16 AM
Feb 04, 25 08:15 AM
Feb 04, 25 08:11 AM